Physical-mechanical performance criteria of cement-soil mortars for earth building coating - Milani, Ana Paula da Silva (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2018)
Soil as a mortar aggregate may improve the physical-mechanical compatibility between the coating system and earth-wall substrate, as well as present greater durability when stabilised with cement. Based on these concepts, the physical-mechanical behaviour of mortars comprising soil, cement, lime and admixture was analysed to be used as coating for earth constructions. Cement-soil mortars using the ratio of sandy soil equal to or less than 1:6 in the cement:soil dosage shows a potential for an application as earth wall coating. However, to improve its workability in the fresh state, it is necessary to add hydrated lime or chemical admixture at a limited proportion so it does not damage the physical performance of the mortar. To qualify the cement-soil mortars for earth building coating, the minimum requirements for volumetric shrinkage, tensile bond strength and compressive strength must be met simultaneously and the following criteria are indicated: minimum compressive strength of 4 MPa; zero volumetric shrinkage index and minimum tensile bond strength of 0.20 MPa.